Oxidative Stress Causes Enhanced Secretion of YB-1 Protein that Restrains Proliferation of Receiving Cells - Andrea Maria Guarino; Annaelena Troiano; Elio Pizzo; Andrea Bosso; Maria Vivo; Gabriella Pinto; Angela Amoresano; Alessandra Pollice; Girolama La Mantia; Viola Calabrò (2018)
The prototype cold-shock Y-box binding protein 1 (YB-1) is a multifunctional protein that regulates a variety of fundamental biological processes including cell proliferation and migration, DNA damage, matrix protein synthesis and chemotaxis. The plethora of functions assigned to YB-1 is strictly dependent on its subcellular localization. In resting cells, YB-1 localizes to cytoplasm where it is a component of messenger ribonucleoprotein particles. Under stress conditions, YB-1 contributes to the formation of stress granules (SGs), cytoplasmic foci where untranslated messenger RNAs (mRNAs) are sorted or processed for reinitiation, degradation, or packaging into ribonucleoprotein particles (mRNPs). Following DNA damage, YB-1 translocates to the nucleus and participates in DNA repair thereby enhancing cell survival. Recent data show that YB-1 can also be secreted and YB-1-derived polypeptides are found in plasma of patients with sepsis and malignancies. Here we show that in response to oxidative insults, YB-1 assembly in SGs is associated with an enhancement of YB-1 protein secretion. An enriched fraction of extracellular YB-1 (exYB-1) significantly inhibited proliferation of receiving cells and such inhibition was associated to a G2/M cell cycle arrest, induction of p21WAF and reduction of Np63 protein level. All together, these data show that acute oxidative stress causes sustained release of YB-1 as a paracrine/autocrine signal that stimulate cell cycle arrest.